Technical-tactical skill assessments in small-sided soccer games: A scoping review - Klingner, F. C.; Huijgen, B. C.; Den Hartigh, R. J. R.; Kempe, M. (International Journal of Sports Science & Coaching, 2022)
Skill assessments are essential to elite soccer coaches and clubs, to provide an evidence-based approach to player evaluation. Valid methods thereby support talent identification and development procedures (e.g. scouting and training strategies). However, it remains a complex challenge. Small-sided games have emerged as a promising tool, due to high ecological validity. Until now, no review has focused on their discriminative power. Therefore, we aimed to investigate whether technical-tactical skill assessments of small-sided games can discriminate between individual players and between teams of different skill levels (i.e. higher vs. lower playing levels and older vs. younger players) in soccer. A scoping review of PubMed, Web of Science, and MEDLINE databases was performed according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews guidelines. A total of 23 studies were included, all but one of which showed at least good methodological quality (i.e. > 50% score in quality assessment). For technical skills, small-sided games indicate discriminative power for passing skills, but only when comparing players of different playing levels, as supported by two of the included studies. Tactical categories, such as movement variability and decision-making, were more pronounced in higher level and more experienced players. However, the most conclusive finding among individual skill assessments was that the technical-tactical overall performance (a total score comprised of different subcategories) of individual players showed a positive relation to skill level in three studies. Team performance assessments in small-sided games showed that older and higher level teams mainly distinguish themselves from less-skilled peers by using the available space more efficiently. With the influence of different assessment instruments and several small-sided games modifications in mind, it may be concluded that technical-tactical skills in small-sided games can discriminate between players and teams of different skill levels. An interesting future avenue is to examine a more consistent approach to skill assessments in small-sided games, which can warrant their use for scouting and talent identification purposes.